2017
DOI: 10.1016/j.healun.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The Giessen Pulmonary Hypertension Registry: Survival in pulmonary hypertension subgroups

Abstract: This is the largest single-center PH cohort described so far. Some parameters used in clinical practice do not independently predict survival. Age, gender and 6MWD outperformed NYHA functional class in predicting survival across all etiologic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
185
5
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(232 citation statements)
references
References 49 publications
21
185
5
6
Order By: Relevance
“…In terms of survival, the findings are similar to those of the PAPUCO study that reported a high rate of mortality at 6 months follow-up [5]. Nonetheless, the overall 3-year survival in this group of patients is 5 to 10% lower than those reported in studies outside Africa [6,[22][23]. This may be attributed to the exclusion of patients with mild PH in this study, as well as the barriers to early diagnosis and treatment of PH in this setting [5].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In terms of survival, the findings are similar to those of the PAPUCO study that reported a high rate of mortality at 6 months follow-up [5]. Nonetheless, the overall 3-year survival in this group of patients is 5 to 10% lower than those reported in studies outside Africa [6,[22][23]. This may be attributed to the exclusion of patients with mild PH in this study, as well as the barriers to early diagnosis and treatment of PH in this setting [5].…”
Section: Discussionsupporting
confidence: 84%
“…Age was one of the prognostic factors for PH mortality. Older age has been shown to place PH patients at an increased risk of mortality [6,22]. The Giessen Pulmonary Hypertension registry demonstrated that age <50 years predicted survival in all PH groups [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data confirm and expand on previous findings by KYLHAMMAR et al [5] and HOEPER et al [4]. Our study broadens the application of this risk assessment tool to SSc-PAH, which typically carries a dismal prognosis compared to other groups [11].…”
supporting
confidence: 92%